Pancreatic Cancer: Pathogenesis and Clinical Studies - Kexun Zhou; Yingping Liu; Chuanyun Tang; Hong Zhu (MedComm)
ABSTRACT Pancreatic cancer (PC) is a highly lethal malignancy, with pancreatic ductal adenocarcinoma (PDAC) being the most common and aggressive subtype, characterized by late diagnosis, aggressive progression, and resistance to conventional therapies. Despite advances in understanding its pathogenesis, including the identification of common genetic mutations (e.g., KRAS, TP53, CDKN2A, SMAD4) and dysregulated signaling pathways (e.g., KRAS–MAPK, PI3K–AKT, and TGF‐β pathways), effective therapeutic strategies remain limited. Current treatment modalities including chemotherapy, targeted therapy, immunotherapy, radiotherapy, and emerging therapies such as antibody–drug conjugates (ADCs), chimeric antigen receptor T (CAR‐T) cells, oncolytic viruses (OVs), cancer vaccines, and bispecific antibodies (BsAbs), face significant challenges. This review comprehensively summarizes these treatment approaches, emphasizing their mechanisms, limitations, and potential solutions, to overcome these bottlenecks. By integrating recent advancements and outlining critical challenges, this review aims to provide insights into future directions and guide the development of more effective treatment strategies for PC, with a specific focus on PDAC. Our work underscores the urgency of addressing the unmet needs in PDAC therapy and highlights promising areas for innovation in this field.